Pracownicze Plany Kapitałowe w praktyce : opłacalność programu — jego główne wady i zalety - Koćwin, Julitta (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The aim of the article was to present the basic assumptions of the Pracownicze Plany Kapitałowe program and to draw attention to the issue of its success and profitability for future pensioners. This program advertised as a pro social one by the ruling party in fact may not be one. The article tried to find the answer to the question of what are the intentions of the government and what the main purpose of the program is. Is it aimed at financial security for future pensioners or at feeding the declining financial market? So far, attention was drawn to the main advantages and disadvantages of this program, analyzed from the point of view of “who will benefi t the most from it.”
Keywords: PPK; third pillar; pension; pension funds; savings